The effects of isobaric and hyperbaric bupivacaine on maternal hemodynamic changes post spinal anesthesia for elective cesarean delivery: A prospective cohort study - Helill, Shamill Eanga (PLoS One, 2019)
BACKGROUND: Spinal anesthesia is a form of regional anesthesia frequently used in various lower abdominal, orthopedic, obstetric operations such as a cesarean delivery. The most common local anesthetic used for spinal anesthesia in obstetric and non-obstetric surgery is bupivacaine which can be utilized as an isobaric or hyperbaric solution, producing differences in maternal hemodynamic changes. Against this backdrop, the study aims to compare the effects of isobaric and hyperbaric bupivacaine on maternal hemodynamic alterations after administering spinal anesthesia for elective cesarean delivery at Gandhi Memorial Hospital, Addis Ababa, Ethiopia. METHODS: A hospital-based prospective cohort study design was employed for the period December 1, 2017 to January 30, 2018. A total of 100 parturient were involved, with one group exposed to isobaric bupivacaine and the other to hyperbaric bupivacaine to observe their effects on maternal hemodynamic changes post spinal anesthesia. The participants were selected through systematic random sampling. Data analysis was performed using SPSS (version 20) through descriptive statistic, independent sample t-test, Mann-Whitney U-test, Fisher’s exact test, and Chi-square test were used. P values of <0.05 was assumed as statistically significant for all tests. RESULTS: The incidence of hypotension was found to be greater in isobaric than hyperbaric groups (82% vs. 60% respectively; p = 0.015). No statistical significant differences were found in mean arterial pressure value at baseline, but, statistically significant changes were observed among the groups (p <0.05) at all study timing after spinal anesthesia, except at 30(th)min. No statistically significant differences were seen in the mean heart rate variability after spinal anesthesia at all periods, except the 15th minute (p = 0.033). A greater rate of vasopressor was used in the isobaric group as compared to the hyperbaric group (36% vs. 14% respectively; p = 0.011). CONCLUSION: Baricity is a significant factor in maternal hemodynamic changes in the parturient for elective cesarean section. Isobaric bupivacaine produces greater change in blood pressure and incidence of hypotension and entails a greater vasopressor requirement than hyperbaric bupivacaine after spinal anesthesia for elective cesarean section.